Non-Competitive Reversible Inhibition of Laccase by H2O2 in Osmium Mediated Layer-By-Layer Multilayer O2 Biocathodes. Issue 9 (1st January 2015) - Grattieri, Matteo; Scodeller, Pablo; Adam, Catherine; Calvo, Ernesto J.
Abstract : A systematic study of the inhibition of laccase by hydrogen peroxide in oxygen biocathodes composed of layer-by-layer self-assembled multilayers of Trametes-trogii laccase and osmium derivatized poly(allylamine) redox mediator has been accomplished using a rotating disc electrode at different electrode potentials, oxygen partial pressures and hydrogen peroxide concentrations. The experimental results are consistent with a reversible non-competitive inhibition mechanism in agreement with the Solomon mechanism for laccase previously reported.